A mixed methods study of affective well-being among SME employees in Malaysia - Yap, Wai Meng (2024)
It is essential for organisations to prioritise the affective well-being of their employees, considering the interplay between affective well-being, mental health, and positive organisational outcomes. Yet, the literature on affective well-being has been minimal and in need of more focused research. Similarly, meaning at work, an important construct in employees' well-being research, faces a dearth of research, especially meaning at work in SMEs. Given that previous studies have advocated for research focused on SMEs, as findings based on large organisations are not transferrable to smaller organisations (Heneman et al., 2000), this research focuses on SMEs. The minimal research on affective well-being among SMEs in Malaysia has formed the basis for a qualitative research design to be adopted, which is the empirical study 1. This study seeks to explore the affective well-being of SME employees. The absence of research on the meaning at work among SMEs, has formed the background for the conceptualisation ofstudy 2. The study examines how participants define meaning at work, and how their respective organisations allow or does not allow them to have meaning at work. From the findings of empirical study 1 and study 1, a conceptual framework was devised, and the corresponding variables were tested in a quantitative design which is the empirical study 3.